2018
DOI: 10.1155/2018/9752736
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Self-Care Behaviors among Low Health Literacy Hypertensive Patients Based on Health Belief Model in Bushehr District, South of Iran

Abstract: The aim of this study was to determine the factors influencing adherence to self-care behaviors among low health literacy hypertensive patients based on health belief model. A cross-sectional study was conducted among 152 hypertensive patients with low health literacy. Patients with limited health literacy were identified by S-TOFHLA. The data were collected using H-scale for assessing self-care behaviors and, HK-LS for assessing knowledge of hypertension. A researcher-made questionnaire was applied for collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 25 publications
4
38
0
2
Order By: Relevance
“…Shiloh, Wade, Roberts, Alford, and Biesecker (2013) found out many findings, the most interesting of which are: there are significant differences in risk perceptions and concern about diseases; there are significant gender differences in risk perceptions and concern about common diseases. Similar results were possible to find in the studies of Duncan, Schaller, andPark (2009), Fukukawa, Oda, Usami, andKarahito (2014), Hill, Boehm, and Prokosch (2016), Larki, Tahmasebi, and Reisi (2018) and Oda (2017). The similar research was done by Welling, Conway, Bebruine, and Jones (2007) with the result, that men and women who perceived themselves to be vulnerable to disease have stronger preferences for apparent health in dynamic faces than individuals who perceive themselves to be relatively less vulnerable to disease.…”
Section: Introductionsupporting
confidence: 83%
“…Shiloh, Wade, Roberts, Alford, and Biesecker (2013) found out many findings, the most interesting of which are: there are significant differences in risk perceptions and concern about diseases; there are significant gender differences in risk perceptions and concern about common diseases. Similar results were possible to find in the studies of Duncan, Schaller, andPark (2009), Fukukawa, Oda, Usami, andKarahito (2014), Hill, Boehm, and Prokosch (2016), Larki, Tahmasebi, and Reisi (2018) and Oda (2017). The similar research was done by Welling, Conway, Bebruine, and Jones (2007) with the result, that men and women who perceived themselves to be vulnerable to disease have stronger preferences for apparent health in dynamic faces than individuals who perceive themselves to be relatively less vulnerable to disease.…”
Section: Introductionsupporting
confidence: 83%
“…No significant predictors were found in the model of the elders without chronic diseases. A possible explanation is that the self-treatment for acute diseases is common across the population groups with low selfperceived health risks, including the people without chronic diseases [48,49]. In addition, it should be noted that the small sample size (N = 85) in this subgroup may lead to the inadequate power of test, which might result in the false negatives of some variables [50].…”
Section: Comparison Between Subgroups Of Elders With and Without Chromentioning
confidence: 99%
“…As for the self-care habit in TCM, on the one hand, people with the habits of self-care may have high perceived susceptibility and are likely to seek professional help instead of the risky self-treatment approaches. Some studies indicated that the self-care practice of some patients with chronic diseases is associated with the high perceived susceptibility of disorders [48,49]. On the other hand, elders with the habits of self-care in TCM have higher affinities to TCM [34], and these elders tend to seek medical help in TCM sectors, in which they may be confronted with less barrier during the process of seeing and communicating with doctors compared to the western medicine sectors [51,52], especially for empty-nest elders without support from younger family caregivers [12].…”
Section: Subgroups Of Empty-nest and Non-empty-nest Eldersmentioning
confidence: 99%
“…Therefore, the association is reasonably stronger between the utilisation of family practice and the less likelihood to self-treat among elders with chronic diseases compared with the result of the model of the whole sample. As for the subgroups of the elders without chronic diseases, a possible explanation for the insignificant model is that the self-treatment for acute diseases is common across the population with low self-perceived health risks [44,45]. Another explanation may relate to the bias from the low rates of the awareness of the presence of the chronic diseases among the rural elders in China, especially in rural areas [46].…”
Section: Subgroups Of Elders With and Without Chronic Diseasesmentioning
confidence: 99%
“…Another possible explanation is that the people with the habits of self-care may have high perceived susceptibility and are likely to seek professional help instead of the risky self-treatment approaches. Some studies indicated that the self-care practice of some patients with chronic diseases is associated with the high perceived susceptibility of disorders [44,45] . The association between self-treatment and the recent alcohol consumption is significant in the subgroup of non-empty-nest elders, which is insignificant in the model of its counterpart.…”
Section: Subgroups Of Empty-nest and Non-empty-nest Eldersmentioning
confidence: 99%